Poxviral vectors for cancer immunotherapy - Kim, Joseph W. (2012)
INTRODUCTION: Poxviral vaccines have been given to over 1 billion people in the successful global eradication of smallpox. Since then, recombinant poxviruses have been investigated extensively as a novel immunotherapy for cancer, undergoing several iterations to optimize their immunogenicity and efficacy. The current platform expressing multiple costimulatory molecules plus a tumor-associated antigen such as PSA, i.e., PSA-TRICOM (PROSTVAC-V/F), is promising and is currently in a phase III randomized, placebo-controlled clinical trial in metastatic castration-resistant prostate cancer. AREAS COVERED: This review discusses the clinical development of poxviral-based cancer vaccines, with a particular focus on the rationale for combining vaccines with other treatment modalities, including radiotherapy, chemotherapy, hormonal therapy, other immune-based therapies, and molecularly targeted therapy. We also discuss the importance of appropriate patient selection in clinical trial design. EXPERT OPINION: Preclinical and early clinical studies with poxviral vector vaccines have shown promising results with this novel immunologic approach both as vaccine alone and combined with other therapies. The challenges of translating the science of immunotherapy to clinical practice include clinical trial design that includes appropriate patient selection, appropriate endpoints, and identification of meaningful surrogate biomarkers.